Uso de antibióticoterapia empírica prolongada asociada a Enterocolitis necrotizante en prematuros en el servicio de Neonatología en el Hospital Belén de Trujillo - Velasco Nalvarte, Ana Lucía (2022)
Neonatal necrotizing enterocolitis (NNS) is a serious gastrointestinal disease in newborns. Necrotizing enterocolitis is one of the complications observed in neonates with extreme prematurity and very low birth weight and is responsible for a considerable burden of morbidity and mortality in this highly vulnerable group. In this sense, it is important to identify the variables related to her, in particular, those modifiable characteristics.